Tales of folk & fey eaudiobook A wicked lovely collection. - Marr, Melissa (Wicked Lovely., 2019)
Return to the world of Wicked Lovely! Listen to an all-new Dark Court short story. "Love Hurts" catches up with Irial, Niall, and Leslie—and offers clues about the Wicked Lovely prequel novel Cold Iron Heart . Tales of Folk & Fey also includes "Old Habits" and "Stopping Time" (previously published Wicked Lovely Dark Court stories) and two previously published selchie short stories ("Awakened" and "Love Struck"). As a bonus, the collection also includes "Carnival of Lies," a prequel story to the 2012 novel Carnival of Secrets .